Novel Endoscopic Approaches to Treating Chronic Obstructive Pulmonary Disease and Emphysema - Gompelmann, D.; Eberhardt, R.; Herth, F. J. F. (Seminars in Respiratory and Critical Care Medicine, 2015)
Chronic obstructive pulmonary disease (COPD) is a widespread disease associated with high morbidity and mortality. The principal aim of therapy is preventing disease progression. Besides rehabilitation and pharmacological treatment, different endoscopic approaches were developed in the past decade extending the therapeutic spectrum. Various endoscopic lung volume reduction (ELVR) techniques are available that differ in the implementation, mechanism of action, complication spectrum, and reversibility. So far, the data on efficacy and safety are variable and still very limited. The most comprehensive data are available for endoscopic valve therapy. This reversible technique leads to lobar atelectasis and thus significant lobar volume reduction in patients with severe emphysema and low collateral ventilation. Implantation of coils leading to parenchymal compression and bronchoscopic thermal vapor ablation inducing an inflammatory reaction are nonblocking ELVR techniques and thus independent of collateral ventilation. Besides ELVR techniques, targeted lung denervation has evolved as the latest development in the field of endoscopic therapy in COPD. The aim of this endoscopic method is sustainable bronchodilation by minimizing the influence of parasympathetic pulmonary nerves on smooth muscles of the airways. This review summarizes the different endoscopic procedures, their mechanism of action, and the results of the clinical trials including efficacy and safety.
Keywords: endoscopic lung volume reduction; endoscopic valve therapy; thermal vapor ablation; collateral ventilation; emphysema; targeted lung denervation